Upregulation of CCT3 predicts poor prognosis and promotes cell proliferation via inhibition of ferroptosis and activation of AKT signaling in lung adenocarcinoma - Kun Wang; Jian He; Changling Tu; Hui Xu; Xugang Zhang; Yongchang Lv; Chao Song (BMC Molecular and Cell Biology, 2022)
Abstract Background Chaperonin containing TCP1 subunit 3 (CCT3) acts as an oncogene in cancers, whereas its role and underlying mechanisms in lung adenocarcinoma (LUAD) are poorly understood. This study investigated the clinical relevance and function of CCT3 in LUAD. Methods Clinical relevance of CCT3 in LUAD and lung squamous cell carcinoma (LUSC) was analyzed based on TCGA database. qRT-PCR and Western blot were used to detect mRNA and protein expression, respectively. CCK8 and colony formation were performed to measure cell viability. PI and PI/Annexin V-FITC assay kit was used to determine cell cycle and cell death, respectively. Luciferase activity was performed to check whether CCT3 regulated slc7a11’s transcription activity. Ferroptosis was determined by incubating the cells with ferroptosis and apoptosis inducer, their inhibitor and autophagy inhibitor, followed by cell viability examination. Results We found that CCT3 was overexpressed in LUAD and LUSC tissues. Overexpression of CCT3 predicted the poor prognosis of LUAD patients. Loss-of-function and gain-of-function experiments demonstrated that CCT3 promoted the proliferation and colony formation of LUAD cells. In addition, CCT3 promoted cell cycle progression and suppressed slc7a11-mediated cell ferroptosis, but not apoptosis. We also found that CCT3 activated AKT. MK2206 significantly reduced the viability of CCT3 overexpressed LUAD cells, while had smaller inhibitory effect on the proliferation of control cells, suggesting that CCT3 dictates the sensitivity of LUAD cells to AKT inhibition. Conclusion Our study demonstrates that CCT3 contributes to the proliferation and growth of LUAD cells through inhibition of ferroptosis and activation of AKT.